The Effects of Orthography on the Pronunciation of Nasal Vowels by L1 Japanese Learners of L3 French: Evidence from a Longitudinal Study of Speech in Interaction - Cyrille Granget; Cecilia Gunnarsson; Inès Saddour; Clara Solier; Vera Serrau; Charlotte Alazard (MDPI AG, 2024)
In recent decades, a vast literature has documented crosslinguistic influences on the acquisition of L2 phonology and in particular the effects of spelling on pronunciation. However, articulating these research findings in terms of taking into account the effects of L1 phonology and spelling on L2 pronunciation in language teaching remains to be examined. These studies are based on experimental cross-sectional methods and mainly focus on L2 English learning by speakers of languages with an alphabetic system. In French, there are few studies on crosslinguistic influences on the acquisition of the nasal vowels (//, // and /<semantics><mover>ε~</mover></semantics>/) and few experimental studies that point to a possible effect of orthography on the pronunciation of these phonemes. The results of experimental studies are difficult to transpose to the language classroom because they are based on word or sentence reading and writing activities, which are quite far-removed from the conversational activities practised in the classroom in interaction with peers and the teacher. Hence, we opted here for a case study of the effect of spelling on the production of nasal vowels in interaction tasks. We conducted a longitudinal study during the first year of extensive learning of French (4 h 30 per week). The results of a perceptive analysis by expert listeners show that (i) learners spell nasal vowels with an <n> or <m> in 98% of the obligatory contexts; (ii) most nasal vowels are perceived as nasal vowels in speech (72%), the others being perceived as vowels followed by a nasal consonant (19.5%) or as oral vowels (8.5%); (iii) consonantisation is stronger when the learner spontaneously produces a word than when (s)he repeats it, (iv) which decreases with time (learning effect) and varies (v) according to the consonant, /<semantics><mover>ε~</mover></semantics>/ being less consonantised than // and //. Finaly, we propose a didactic discussion in the light of intelligibility and influence of orthography.